The effect of hawgent dynamic mathematics software on mathematics achievement: A meta-analysis - Li, Xinxin; Zhou, Ying; Wijaya, Tommy Tanu (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
In recent years, ICT development has greatly affected the education sector. The development has provided many opportunities to innovate and improve the quality of education. Dynamic mathematics software is one of the learning media that is widely used in mathematics lessons. China has always wanted to be innovative by developing Hawgent Dynamic Mathematics software with more features than other dynamic mathematics software. This research aims to determine the effect of Hawgent Dynamic Mathematics software on mathematics achievement and analyze the advantages of Hawgent compared to other dynamic mathematics software. This research employed a meta-analysis approach by analyzing 28 empirical research articles published in both Chinese and foreign journals. There are 46 effect sizes with 4137 students from 2018 to 2021. Furthermore, the data was obtained using CMA software. The results showed that the effect size of Hawgent on mathematics achievement was 2.11 (P=0.00<0.1), within the very high category. Further analysis showed that the number of students did not affect Hawgent’s effect size. The effect of Hawgent at the senior high school level was greater than at the elementary and junior high school levels. Furthermore, Hawgent’s effect on geometry and algebra subjects was greater than any other subjects. This research can be useful as information on the development of dynamic mathematics software since many countries tend to use Geogebra and Geometric Sketchpad.